Peramalan Kebutuhan Air: Analisis Debit Kebutuhan Air Bersih pada Masa Mendatang - Anggi Nidya Sari; M. Ade Surya Pratama; Viktor Suryan (Jurnal Talenta Sipil, 2023)
Bengkulu City is one of the cities of Bengkulu Province. Bengkulu is classified as big city in terms of number of population with 374.694 people. Increasing number of populations effected the needs of water as basic necessity. However, enlargement of water needs contradictive with amount of water on global. The reduction in water catchment areas and the amount of pollution decreasing water that is suitable for consumption. Hence, this research aims to predict future water needs as a measure to anticipate a shortage of water supply. Forecasting of the amount of water demand in this study uses a descriptive quantitative method. The result shows the amount of water demand discharge in 2031 is 28.218 Litre/second. So, the amount of discharge of water demand in 2031 will increase by 0.61% from 2021.